Rekonstruksi Konstitusionalisme Digital Sebagai Dasar Pengaturan Artificial Intelegence dalam Sistem Ketatanegaraan Indonesia - Mutia Nur Fadhilah Ruslan (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
The rapid development of Artificial Intelligence (AI) has introduced significant challenges to Indonesia’s constitutional system, particularly in relation to the protection of constitutional rights, state accountability, and legal certainty within the digital sphere. This study aims to examine the urgency of reconstructing digital constitutionalism as a normative foundation for AI regulation in Indonesia and to formulate a regulatory model that is consistent with the values of Pancasila and the 1945 Constitution of the Republic of Indonesia. The research employs a normative legal method using statutory, conceptual, comparative, and case approaches. Legal materials consist of legislation, judicial decisions, scholarly literature, and international instruments concerning AI governance. Data are analyzed qualitatively through legal interpretation and comparative analysis of digital constitutionalism frameworks in the European Union, South Korea, and Indonesia. The findings reveal that AI regulation in Indonesia remains fragmented and sectoral, lacking a comprehensive legal framework, thereby creating legal uncertainty, regulatory inconsistency, and insufficient protection of citizens’ constitutional rights. This study proposes the reconstruction of digital constitutionalism through the concept of a digital constitution as a constitutional framework (meso-norm) that bridges the fundamental values of Pancasila and the 1945 Constitution with future AI legislation. Furthermore, it introduces an AI governance model integrating principle-based regulation and risk-based regulation, supported by constitutional oversight, algorithmic transparency, accountability, digital rights protection, and effective institutional arrangements. This model is expected to provide a conceptual foundation for the enactment of a comprehensive Artificial Intelligence Law capable of establishing constitutional, adaptive, and human-centered AI governance while safeguarding constitutional rights in Indonesia